BaSO4-Epoxy Resin Composite Film for Efficient Daytime Radiative Cooling - Wu, Tengfei (Langmuir : the ACS journal of surfaces and colloids, 2024)
Conventional cooling methods are based on active cooling technology by air conditioning, which consumes a large amount of energy and emits greenhouse gases. Radiative cooling is a novel promising passive cooling technology that uses external space as the cooling source and requires no additional energy consumption. Herein, we propose an approach to prepare highly dispersed BaSO4 nanoparticles (NPs) using a direct precipitation method combined with the in situ surface modification technology. The as-prepared PVP-modified BaSO4 NPs with an average size of 20 nm can be stably dispersed in ethanol for more than 6 months and then were used as building blocks to prepare spherical BaSO4 clusters with an average size of 0.9 μm using a scalable spray drying technique. The BaSO4 NPs/clusters (mass ratio 1:1) were used for preparing radiative cooling epoxy resin film, showing a high solar reflectance of 71% and a high sky window emissivity of 0.94. More importantly, this composite film displays superior radiative cooling performance, which can reduce the ambient temperature by 13.5 °C for the indoor test and 7 °C for the outdoor test. Compared with the commercial BaSO4 filled film, our BaSO4-epoxy resin composite film offers advantages not only in radiative cooling but also in mechanical properties with a 16.6% increase of tensile strength and 40.1% increase of elongation at break, demonstrating its great application potential in the field of building air conditioning